What can be learned from behavioural economics for environmental policy? - Markus Pasche (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2013)
Behavioural economics attracted attention from environmental economists: it should help to understand why people do not respond to environmental policy measures, based on neoclassical assumptions, as predicted by theory. Moreover, understanding motives and driving forces behind pro-social, pro-environmental and cooperative behaviour should help to improve environmental policy design. The aim of this paper is a critical discussion of the way how this branch of research is interpreting the explanatory power and the normative (policy) implications of behavioural economics.
Keywords: B41; D0; D70; Q57; Q58; 330; behavioural economics; environmental economics; policy design; methodology